Evaluation and Management of Primary Hyperparathyroidism: Summary Statement and Guidelines from the Fifth International Workshop. (17th October 2022) - Bilezikian, John P.; Khan, Aliya A.; Silverberg, Shonni J.; Fuleihan, Ghada El‐Hajj; Marcocci, Claudio; Minisola, Salvatore; Perrier, Nancy; Sitges‐Serra, Antonio; Thakker, Rajesh V.; Guyatt, Gordon; Mannstadt, Michael; Potts, John T.; et al.
ABSTRACT: The last international guidelines on the evaluation and management of primary hyperparathyroidism (PHPT) were published in 2014. Research since that time has led to new insights into epidemiology, pathophysiology, diagnosis, measurements, genetics, outcomes, presentations, new imaging modalities, target and other organ systems, pregnancy, evaluation, and management. Advances in all these areas are demonstrated by the reference list in which the majority of listings were published after the last set of guidelines. It was thus, timely to convene an international group of over 50 experts to review these advances in our knowledge. Four Task Forces considered: 1. Epidemiology, Pathophysiology, and Genetics; 2. Classical and Nonclassical Features; 3. Surgical Aspects; and 4. Management. For Task Force 4 on the Management of PHPT, Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) methodology addressed surgical management of asymptomatic PHPT and non‐surgical medical management of PHPT. The findings of this systematic review that applied GRADE methods to randomized trials are published as part of this series. Task Force 4 also reviewed a much larger body of new knowledge from observations studies that did not specifically fit the criteria of GRADE methodology. The full reports of these 4 Task Forces immediately follow this summary statement. Distilling the essence of all deliberations of all Task Force reports and Methodological reviews, we offer, in this summary statement, evidence‐based recommendations and guidelines for the evaluation and management of PHPT. Different from the conclusions of the last workshop, these deliberations have led to revisions of renal guidelines and more evidence for the other recommendations. The accompanying papers present an in‐depth discussion of topics summarized in this report. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).